Conventions And Change in Semantics - Sultanova Dilnoza Saliyevna (Genius Journals, 2022)
This article examines the features of the appearance of semantic changes and conventions and the specifics of their functioning in the territorial version of the language. It defines the mechanism of semantic changes and the degree of influence of the English language on semantics.
Keywords: semantic changes; conventions; mechanism of semantic changes; language forms